Introduction to survey sampling and calibration - Guinand, Mihaela Catalina; Vallée, Audrey-Anne (My University, 2015)
We introduce some basic concepts in survey sampling, defining the common terminology in the field. We touch upon various notions, ranging from the sample selection to questionnaire design and data collection and dissemination. In the first part, special attention is paid to different estimators of some parameters of interest, whereas in the second, they are applied in a technique called “calibration”, whose purpose is to improve the accuracy of the estimations.
, Young Researchers Conference, Université de Neuchâtel